EVALUATION OF BIOPLASTIC FROM BANANA PEELS: A SYSTEMATIC LITERATURE REVIEW - Eka Cahya Muliawati; Dwiky Ari Rahmadi; David Yuliana Sari; Wahyu Wibisono Nur Aminnullah; Haris Fajar Kurniawan; Adinda Jamilatul Lestari; Ivan Maulana Alfandi (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2025)
Bioplastics based on natural materials offer an innovative solution to reduce the negative impact of conventional plastics on the environment. This study evaluated bioplastics made from banana peels processed with various plasticizers, such as glycerol, chitosan, sorbitol, polylactic acid polymer, sodium metabisulfite, and tapioca starch. The focus was on mechanical properties, such as biodegradability, tensile strength, and elongation. Banana peels, with a starch content of 59%, proved ideal for bioplastics, with a degradation time of 4–84 days in soil. Bioplastics with 2% glycerol degraded in 4 days, while those with sodium metabisulfite degraded in 84 days. Glycerol increased flexibility but decreased tensile strength. The combination of 1.5% glycerol and tapioca starch produced the highest tensile strength of 66.39 MPa, while the highest elongation was 115.43% with 2% glycerol. This study highlights the potential of banana peel bioplastic as an environmentally friendly alternative, and further research is recommended to optimize the combination of plasticizers to make the bioplastic stronger, more elastic, and antibacterial by combining glycerol, sodium metabisulfite, and tapioca starch. These findings are important for the future development of sustainable and applicable bioplastics.